Algorithmic Modelling of Advanced Chlorination Procedures for Multimetal Recovery - Lukas Höber; Roberto Lerche; Stefan Steinlechner (Metals, 2021)
In the course of developing an innovative process for CO2-optimised valuable metal recovery from precipitation residues accumulating in the zinc industry or nickel industry, the chlorination reactions were investigated. As the basis of small-scale pyrometallurgical experiments, the selected reaction systems were evaluated by means of thermodynamic calculations. With the help of the thermochemical computation software FactSage (Version 8.0), it is possible to simulate the potential valuable metal recovery from residual materials such as jarosite and goethite. In the course of the described investigations, an algorithmically supported simulation scheme was developed by means of Python 3 programming language. The algorithm determines the optimal process parameters for the chlorination of valuable metals, whereby up to 10,000 scenarios can be processed per iteration. This considers the mutual influences and secondary conditions that are neglected in individual calculations.